Pooled-analysis of tadalafil and tamsulosin for ureteral calculi - Sun, Fengze; Liu, Hongquan; Wu, Gang; Liu, Ming; Liu, Shangjing; Wang, Lin; Zou, Qingsong; Cui, Yuanshan; Wu, Jitao (Frontiers in Pharmacology, 2024)
Objective: UrolithiasisNephrolithiasis is one of the mosta common urological diseases and affects the daily life of patients. Medical expulsive therapy has become acceptable for many parents. We conductedarried out a meta-analysis to determine the efficacy and safety of tadalafil compared with tamsulosin for treating distal ureteral stones less than 10 mm in length. Methods: Related studies were identified via searches of the PubMed, Embase, and Cochrane Library databases. All the articles that described the use of tadalafil and tamsulosin for treating distal ureteral stones were collected. Results: A total of nine 14 studies were included in our meta-analysis. Our results revealed that tadalafil promotedenhanced an increase in the expulsion rate [odds ratio (OR) = 0.68, 95% confidence interval (CI): 0.47 to 0.98, P = 0.04][odds ratio (OR): 0.68, 95% confidence interval (CI): 0.51 to 0.90, P = 0.007]; reducedaccelerated expulsion time [mean difference (MD) = 1.22, 95% CI (0.13, 2.30), P = 0.03][mean difference (MD) = 1.67, 95% CI: 0.60 to 2.74, P=0.002]; lowereddecreased analgesiac need use [MD = 38.66, 95% CI (7.56, 69.77), P = 0.01] (MD = 36.14, 95% CI: 3.79 to 68.50, P=0.03); and hospital visits [MD = 0.14, 95% CI (0.06, 0.22), P = 0.0006] (MD = 0.14, 95% CI: 0.06 to 0.22, P=0.0006). According to our subgroup analysis, either tadalafil 5mg or 10mg didcould not promote expulsion rate and accelerate expulsion time compared with tamsulosin. But patients receiving a low dose of 5 mg tadalafil decreased analgesia usage [MD = 101.04, 95% CI (67.56, 134.01), P < 0.00001].also led to a better expulsion rate (OR=0.50, 95% CI=0.27 to 0.95; P = 0.03) and expulsion time (MD = 2.79, 95% CI=0.70 to 4.89; P=0.009) than did the other doses. A high dose of tadalafil (10 mg) decreased only the expulsion time (MD = 1.23, 95% CI=0.51 to 1.94; P = 0.0008) when headache developed. Conclusion: Compared with tamsulosin, tadalafil demonstratepresents a higher expulsion rate and less expulsion time for patients with promotes expulsion efficiency for distal ureteral stones less than 10 mm in length with a favorable safety profile.